2018
DOI: 10.1038/s41598-018-26190-1
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 system targeting regulatory genes of HIV-1 inhibits viral replication in infected T-cell cultures

Abstract: The CRISPR/Cas9 system provides a novel and promising tool for editing the HIV-1 proviral genome. We designed RNA-guided CRISPR/Cas9 targeting the HIV-1 regulatory genes tat and rev with guide RNAs (gRNA) selected from each gene based on CRISPR specificity and sequence conservation across six major HIV-1 subtypes. Each gRNA was cloned into lentiCRISPRv2 before co-transfection to create a lentiviral vector and transduction into target cells. CRISPR/Cas9 transduction into 293 T and HeLa cells stably expressing T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 68 publications
1
75
0
Order By: Relevance
“…This approach may also be used to specifically knockout or attenuate the HIV-1 provirus, for example, by targeting the LTR to disrupt viral gene expression or excise the integrated genome (Ebina et al, 2013;Hu et al, 2014;Kaminski et al, 2016;Lebbink et al, 2017;Yin et al, 2017;Bella et al, 2018;Wang Q. et al, 2018). Alternatively, various positions of the latent provirus could be targeted by CRISPR-Cas9 to induce multiple non-homologous end joining (NHEJ) associated indels that deactivate the virus through frame shift mutation (Liao et al, 2015;Ueda et al, 2016;Wang et al, 2016;Ophinni et al, 2018). Additionally, recent work has shown that, in combination with a novel drug delivery system, CRISPR-Cas9 directed editing of proviral DNA could effectively eliminate HIV-1 infection in mouse models (Dash et al, 2019).…”
Section: Gene Editingmentioning
confidence: 99%
“…This approach may also be used to specifically knockout or attenuate the HIV-1 provirus, for example, by targeting the LTR to disrupt viral gene expression or excise the integrated genome (Ebina et al, 2013;Hu et al, 2014;Kaminski et al, 2016;Lebbink et al, 2017;Yin et al, 2017;Bella et al, 2018;Wang Q. et al, 2018). Alternatively, various positions of the latent provirus could be targeted by CRISPR-Cas9 to induce multiple non-homologous end joining (NHEJ) associated indels that deactivate the virus through frame shift mutation (Liao et al, 2015;Ueda et al, 2016;Wang et al, 2016;Ophinni et al, 2018). Additionally, recent work has shown that, in combination with a novel drug delivery system, CRISPR-Cas9 directed editing of proviral DNA could effectively eliminate HIV-1 infection in mouse models (Dash et al, 2019).…”
Section: Gene Editingmentioning
confidence: 99%
“…CRISPR/Cas9 technology was first applied to HIV-1 in 2013 [219], with several rapidly ensuing studies (reviewed in [216]). Proviral cleavage by CRISPR was often tested in cell lines, like HEK 293T cells and HeLa [219][220][221][222][223], which unfortunately do not resemble natural targets of HIV. However, this technology was also shown to be effective in more relevant T cell lines [219][220][221][222][223] and in cell line models of HIV-1 latency [220,[222][223][224].…”
Section: Crisprmentioning
confidence: 99%
“…A general ideal is to make two DSBs by nucleases in proviral DNA (e.g., in the LTRs), leading to the removal of the viral genome [250]. Alternatively, targeting conserved and critical viral genes has been found to disable the provirus [251]. Nevertheless, this strategy faces profound challenges, including the diversity of viral quasi-species, the fast mutating nature of HIV-1, the transcriptionally inactive latency, the establishment of latent infection in long-lived cell subsets (such as resident macrophages in various tissues), and the lack of ideal animal models.…”
Section: Hiv-1/aidsmentioning
confidence: 99%